Diasporas and States of origin: the positive experience of interaction - Natalia V. Varlamova; Tatiana A. Vasilieva; Elena A. Sorokina; Elvira V. Talapina; Valentina I. Chekharina (RUDN Journal of Law, 2022)
In today’s world a considerable number of people for one reason or another live outside their (or their ancestors’) States of origin. In most cases they retain a sense of belonging to their Homeland and an interest in maintaining ties with it. In turn, States also seek to develop relations with compatriots living abroad. This direction of State activity in many countries is enshrined at the constitutional level; special laws determining the legal status of compatriots, directions and forms of interaction with them have been adopted; special State programs to support diasporas are being developed and implemented. In general, the policy of States toward compatriots living abroad aims to preserve their national (linguistic, cultural, and religious) identity and to involve them in their social, cultural, economic, and political life. For these purposes, States help compatriots living abroad to study their native language, introduce them to national culture and traditions, support diaspora organizations, develop their cooperation with public authorities, scientific and educational institutions, business communities, and non-profit organizations, encourage investment activity, and, if necessary, provide compatriots with social assistance. Foreign countries have accumulated a lot of positive experience in this regard, and its analysis and generalization is the subject of this article.